2015
DOI: 10.1186/s13638-015-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved time and frequency synchronization in presence of imperfect channel state information

Abstract: This paper addresses altogether time and frequency synchronization in IEEE 802.11a orthogonal frequency division multiplexing (OFDM) wireless communication systems. The proposed algorithms have two main features: (i) they make use of an additional source of information available at IEEE 802.11a physical layer, on top of the usual ones typically adopted for synchronization such as training sequences. This additional source of information is provided by the higher layers of the communication protocol. In fact, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Simulation results compatible with the IEEE 802.11a standard in both indoor and outdoor situations showed that the recommended method significantly improved the performance in terms of synchronization. Bit error rate and failure probability are measured in comparison to the most recent techniques [15].…”
Section: Related Workmentioning
confidence: 99%
“…Simulation results compatible with the IEEE 802.11a standard in both indoor and outdoor situations showed that the recommended method significantly improved the performance in terms of synchronization. Bit error rate and failure probability are measured in comparison to the most recent techniques [15].…”
Section: Related Workmentioning
confidence: 99%
“…A synchronization algorithm, such as [41] or [42], should be considered at the Information Layer Protocol, to keep the same timeline in all the MDP data from every monitoring mote. Usually, the accuracy of the analysis will depend on the precision offered by the synchronization algorithms.…”
Section: Model Descriptionmentioning
confidence: 99%
“…These allow, not only the correct timeline characterization, but also may be fundamental in order to analyze the time constrictions of the system, which is a key characteristic of time critical applications. In this way, last advances in this area [41,42,43] can be applied at this layer to obtain the best results. The used synchronization algorithm must be part of the Information Layer Protocol, which must offer the user the possibility to select the most appropriated synchronization protocol for the characteristics of the monitoring application.…”
Section: Model Descriptionmentioning
confidence: 99%